La sencilla lucidez de Pedro Jorge Vera. Notas a propósito de su cuentística (Homenaje) - Tornés Reyes, Emmanuel (2014)
A privileged genre in Latin America, short stories have had, and still have, highly esteemed cultivators in the region such as the late Ecuadorian writer Pedro Jorge Vera, a creator whose birth centennial is celebrated in 2014, on the occasion of which this paper examines some of his most important stories in order to highlight their humanistic and denunciatory will of the social injustices and prejudices suffered by the poorest and least privileged sectors of Latin America. With their lucid simplicity, Vera’s stories stand out for the stylistic organicity of their writing, the broad thematic spectrum and the rich range of narrative procedures which very effectively convey the charges of the stories told. Distinctive features of this manner of proceeding are the fully developed, the rapid progress of the action and compact structure, the unpredictability of their outcomes, the sobriety and accuracy of the narrative discourse, the decisive role of deconstructive procedures and preference for problematic, contradictory characters.